HUBUNGAN MOTIVASI DENGAN KINERJA PERAWAT PELAKSANA DI RUANG RAWAT INAP RUMAH SAKITUMUM DAERAH SIMEULUE - Baharuddin, Baharuddin; Anasril, Anasril; Bustami, Bustami (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Nursing as a form of professional service is an integral part of overall health services. Quality and professional nursing services are the targets to be achieved to improve quality in hospitals. To improve performance, there are many factors that influence it, one of which is focused on the motivation variable. The purpose of this study was to determine the relationship between motivation and nurse performance at the Simeulue Regional General Hospital. This type of research is descriptive analytic with the research design used is Cross sectional Study, with a sample size of 32 executive nurses taken by cluster random sampling method. Data analysis includes univariate analysis by looking for frequency distribution, and bivariate analysis using the chi-square test with a meaning value (α = 0.05). The results showed that most respondents had motivation in the high category, namely 20 people or around 62.5% and the majority of respondents had performance in the good category, namely 18 people or 56.2%. From the results of bivariate analysis showed the results that there was a relationship between motivation and the performance of executive nurses with a p value = 0.017 (p <0.05). It is recommended to nurses at Simeulue Hospital to further increase work motivation and implement good performance according to procedure in serving patients and trying to meet patient expectations